HUBUNGAN ANTARA EFIKASI DIRI DENGAN PROKRASTINASI AKADEMIK PADA MAHASISWA BK UPGRIS ANGKATAN 2019 - Iis hidayah; Heri Saptadi Ismanto; Agus Setiawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
College students have a varied academic workload so that some college students delay completing their academic assignments. Various things that cause procrastination behavior among BK UPGRIS class of 2019 college students in carrying out lectures are influenced by a lack of understanding of the material obtained, laziness in studying, playing with friends and study time being used for other activities that are more fun or entertaining. So this is a delaying factor in completing the lecture process, BK UPGRIS class of 2019 students are expected to have high self-efficacy so that they can motivate and encourage themselves to be more active in completing their studies. This research is a quantitative study which aims to determine the relationship between self-efficacy and academic procrastination in BK UPGRIS college students class of 2019. The research subjects in this study were 112 college students, sampling in this study used a proportional incidental sampling technique. The self-efficacy variable is measured using a scale based on aspects of Bandura's self-efficacy which consists of 32 items, while the academic procrastination variable is measured using a scale, namely a scale based on aspects of Ferrari which consists of 27 items. The data were analyzed using the Pearson Product Moment correlation analysis technique and obtained the results of Pearson Correlation = -0.661 with a significance level of 0.000 (p<0.05), indicating that there is a negative relationship between self-efficacy and academic procrastination, which means that the higher the self-efficacy, the greater the low academic procrastination, conversely if self-efficacy is low then college students' academic procrastination will tend to be high.